2001
DOI: 10.1073/pnas.131627698
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical hierarchy in transition states: Why and how does a system climb over the mountain?

Abstract: How a reacting system climbs through a transition state during the course of a reaction has been an intriguing subject for decades. Here we present and quantify a technique to identify and characterize local invariances about the transition state of an N-particle Hamiltonian system, using Lie canonical perturbation theory combined with microcanonical molecular dynamics simulation. We show that at least three distinct energy regimes of dynamical behavior occur in the region of the transition state, distinguishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
96
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 87 publications
(101 citation statements)
references
References 34 publications
5
96
0
Order By: Relevance
“…The blue dotted line shows the reaction probability calculated by the Gaussian approximation for y 1 , that is, only the terms in the first bracket in Eq. (25). The red solid line is calculated by the Gram-Charlier A series up to the cubic term [n = 3 in Eq.…”
Section: A Reaction Probabilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The blue dotted line shows the reaction probability calculated by the Gaussian approximation for y 1 , that is, only the terms in the first bracket in Eq. (25). The red solid line is calculated by the Gram-Charlier A series up to the cubic term [n = 3 in Eq.…”
Section: A Reaction Probabilitiesmentioning
confidence: 99%
“…45 The validity of the usage of perturbation theory to take into account such nonlinearity in the region of rank-one saddle has been ensured by several studies in experiments 46,47 and theories [48][49][50][51][52][53][54][55][56][57] on the regularity of crossing dynamics over the saddle and the corresponding phase space geometrical structure (e.g., a no-return TS) in a wide class of Hamiltonian systems. [4][5][6][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] One can naturally adopt this perturbation theory without loss of generality as far as the total energy of the system is not so very high that any perturbation treatment is invalidated. These developments, however, are all based on the Hamiltonian formalism, which corresponds to isolated systems (i.e., gas phase).…”
Section: Introductionmentioning
confidence: 99%
“…LCPT has been applied to seeking for such local descriptions in a perturbative manner from integrable solutions, and shown to be versatile in various types of Hamiltonian in the research fields such as celestial mechanics [26,27], atomic physics [28,29], cluster physics [30][31][32][33][34][35][36]. For example, in the context of chemical reaction dynamics, LCPT has been applied to seeking (locally-)no-return transition state and the associated reaction coordinate buried in the phase space for many-degrees of freedom Hamiltonian systems such as intramolecular proton transfer in malonaldehyde [37,38], argon cluster isomerization [30][31][32][33][34][35][36], O( 1 D) + N 2 O → NO + NO [39], a hydrogen atom in crossed electric and magnetic fields [29,40], HCN isomerization [41,42,1,2], and so forth. LCPT was generalized to dissipative systems such as multidimensional (generalized) Langevin formulation to describe reactions under thermal fluctuation, in which no-return transition state can be obtained by incorporating nonlinearity of the system and interactions with heat bath [43][44][45][46][47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…While H 0 can take any kind of functional form, recent studies [7][8][9][22][23][24][25][26][27] have found that it is possible to introduce a coordinate transformation ðx; $; q 2 ; . .…”
mentioning
confidence: 99%
“…(4) is called ''partial normal form'' (PNF) in the sense that only the action of the reactive mode is transformed as an invariant, which survives robustly even at a moderately high energy regime (because resonance does not meet between the reactive and nonreactive modes [7][8][9][22][23][24][25][26][27]). It is also possible to construct a ''full normal form'' that makes all the actions transform as invariants of motion [7][8][9][10][22][23][24][25].…”
mentioning
confidence: 99%